2004
DOI: 10.1097/00005537-200401000-00022
|View full text |Cite
|
Sign up to set email alerts
|

Smoking in Chronic Rhinosinusitis: A Predictor of Poor Long‐Term Outcome After Endoscopic Sinus Surgery

Abstract: Smoking is associated with statistically worse outcomes after ESS based on average SNOT-16 scores. Although no investigator has proved that the effects of smoking on sinonasal health are reversible, we counsel smoking patients considering ESS about the desirability of smoking cessation (for this and many health reasons), and the possibility of a poorer postsurgery outcome should they continue smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
84
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(95 citation statements)
references
References 15 publications
9
84
1
1
Order By: Relevance
“…Patients with allergic rhinitis who have ever smoked have a 43-fold risk to have nasal polyps [23]. Smoking proved to play a significant role in outcome after FESS in adults [8,13]. Several authors have reported the role of passive smoking in children in CRS after FESS [29].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with allergic rhinitis who have ever smoked have a 43-fold risk to have nasal polyps [23]. Smoking proved to play a significant role in outcome after FESS in adults [8,13]. Several authors have reported the role of passive smoking in children in CRS after FESS [29].…”
Section: Discussionmentioning
confidence: 99%
“…In 1994, the Surgeon General suggested that tobacco exposure contributes to CRS through ‘aggravation and prolongation of sinusitis' [12]. Several studies have suggested that smokers have worse outcomes after functional endoscopic sinus surgery (FESS) when compared to nonsmokers, including a higher revision rate for smokers compared to nonsmokers, smoking as a significant factor in reasons for revision surgery, decreased postoperative endoscopic scores in smokers, increased revision rates in children exposed to secondhand smoke and worse long-term 20-item sinonasal outcomes test (SNOT-20) scores in smokers [13,14,15,16,17]. Our data previously published in ‘The effects of smoking on short-term quality of life outcomes in sinus surgery' [18] demonstrated that smokers actually achieved greater short-term benefits compared to nonsmokers.…”
Section: Introductionmentioning
confidence: 99%
“…A doseresponse like relationship between CS and upper respiratory conditions such as rhinitis, impaired olfaction, and sleep disturbances has also been described [26,31,32]. Further, exposure to cigarette smoke seems to be a contributory factor in chronic rhinosinusitis [9,33], with negative impact on outcome after FESS, both in adult populations (active smokers), and in pediatric populations (passive smokers) [33][34][35][36], although some studies have reported contradictory results [11,14,37]. Our study expands upon previous knowledge and adds new evidence of adverse upper respiratory effects associated with CS: in subjects seeking medical attention due to chronic upper airway complaints, CS seems to be an important determinant.…”
Section: Discussionmentioning
confidence: 93%